DESIGNING TECHNOLOGY-ASSISTED LESSON MATERIALS FOR ESP NURSING STUDENTS BY USING TPACK - Sitepu, Sarfita; Masela, Maximeliana; Kurniawati, Lemmuela Alvita (Universitas Negeri Makassar, 2020)
Abstract. The main purposes of this research is to design technology-assisted lesson materials for nursing students by using TPACK. English for Specific Purposes (henceforth, ESP) for nursing students focuses on preparing students to use English in their academic field and support their professions in their future career as a nurse. Conducted in one of private health science schools in Yogyakarta, this research employed Research and Development (henceforth, R&D) as the method. Needs analysis by using interviews and observations were done to gather the data. The research participants were one English teacher and 45 nursing students of the third semester of the respective institution. In addition to the research method, Analysis, Design, Development, Implementation, and Evaluation (henceforth, ADDIE) framework was adopted to design the lesson materials. The results of the research indicated that the students showed their needs and interests in using technological tools during their learning process; this was revealed through the results of the needs analysis conducted at the beginning of the research. Secondly, the technological tools implemented by using TPACK framework seem to empower the students during the learning process; they got more confident in engaging the classroom activities and participated more actively in class. The results of this research will provide insight for ESP teachers in designing technology assisted lesson materials and instructional activities by using TPACK framework. Moreover, ESP teachers might consider to implement TPACK framework to build blended learning environment in facilitating student learning.